Community participation in Karawang Regency in the Midwife Independent Practice vaccination program by the Office of Population Control and Family Planning - Bunga Shafira Rizqia Pratami Rosyidi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The increasing number of positive Covid-19 in Indonesia is still there. West Java Province itself is still in the category of contributing the most Covid-19 patients in Indonesia, one of the areas that contributes the most patients is Karawang Regency. The government's effort to reduce the positive number of Covid-19 is to provide immediate vaccination to all Indonesian people. To accelerate the distribution of vaccinations to the community, the National Population and Family Planning Agency (BKKBN) created a family-based vaccination program. The pilot area for this program is Karawang Regency, BKKBN is working with the Karawang Regency Population Control and Family Planning Agency (DPPKB) to help realize the family vaccination program. The PPKB Office itself involved midwives in each sub-district for this program. With the family vaccination program, the participation of people who want to be vaccinated is increasing rapidly, and this is very helpful for the Karawang Regency Government to accelerate the distribution of vaccinations evenly in Karawang Regency